Evaluation of the Fire-Free Village Program on Forest and Land Fires in Pelalawan Regency (Case Study: Segati Village) - Hafiz Hazalin Sinaga; Ridwan Manda Putra; Muhammad Syafii; Budijono Budijono (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Forest and land fires pose a serious threat to Pelalawan Regency, undermining environmental sustainability and community well-being. The Fire-Free Village (FFV) program serves as a preventive initiative that promotes active community participation and institutional collaboration. This study aims to analyze internal and external factors influencing the effectiveness of the FFV program and to formulate strategies for strengthening its implementation and adaptability to local conditions. A mixed-methods approach combined with SWOT analysis was employed, focusing on five program-supported villages. The findings indicate that strengths such as strong community participation and government policy support serve as key assets. At the same time, weaknesses and threats include limited resources and the persistent culture of land burning. Optimization strategies include enhancing human resource capacity, developing alternative economic activities, improving early-detection technologies, and promoting education grounded in local cultural values. These findings contribute significantly to the development of more effective and sustainable forest and land fire prevention strategies in Pelalawan Regency.